Coincidental Central Precocious Puberty and Wilms Tumor in a 5-Year-Old Girl - Laura Kasongo; Patricia Forget; Ramona Corina Nicolescu (Case Reports in Pediatrics)
Wilms tumor is the most frequent pediatric renal malignancy, and its usual presentation is an abdominal mass or hematuria. Unusual presentations have also been reported, such as paraneoplastic syndromes (acquired von Willebrand disease, sudden death due to pulmonary embolism, and Cushing syndrome). These conditions can precede, occur concomitantly, or present in a later phase of tumor development. Precocious puberty, as paraneoplastic endocrine syndrome, has already been described in children with malignant tumors (brain, gonadal, adrenal tumors, and hepatoblastoma). However, little is known about central precocious puberty, as paraneoplastic manifestation of nephroblastoma or secondary to its specific chemotherapy. Here, we report a case of Wilms tumor and simultaneous precocious puberty in a 5-year-old girl. The initial diagnosis was premature telarche, but the clinical and biological pubertal progression changed our diagnosis to idiopathic central precocious puberty. Chemotherapy and nephrectomy were well tolerated, and we began treatment with a gonadotropin-releasing hormone agonist which showed favorable outcomes over the short term. We highlight the need for early diagnosis and work-up in all patients of precocious puberty, in order to institute timely management.